(untitled) (Archives of Pediatrics of Uruguay, 2021)
Introduction: inappropriate prescription of antibiotics (ATB) is a public health problem. Objective: to describe the frequency and reasons for the inappropriate use of ATB in children hospitalized in the Moderate Care Ward of the Pereira Rossell’s Pediatric Hospital Center between 06/15/2019 and 07/15/2019. Materials and Methods: descriptive, cross-sectional study. Children under 15 years of age were included in systemic ATB treatment regardless of the reason for the prescription. Variables: age, comorbidities, diagnosis at discharge, ATB (type, dose, route, interval, duration). Inappropriate use was categorized into: type A (selection of inappropriate ATB) and type B (ATB not indicated). Results: 100 children were included, 53% female, median age 2.2 years (range 0-14), 52% had comorbidities. Inappropriate prescription was detected in 43%, category A 30% and category B 13% (p <0.05). The main cause of inappropriate prescription was respiratory infections (33%). Prevalence of appropriate prescription was observed for the case of children under one year of age and inadequate in those over 5 years of age (p <0.05). In category A (n = 30), the most frequent cause of inadequate prescription was the use of ATB with a greater spectrum than required (14/30) followed by intravenous administration (5/30). The most frequently inappropriately prescribed ATBs were ampicillin (17/43) and ceftriaxone (14/43). Conclusions: the inappropriate prescription of ATB in this center is a frequent problem. The main pattern is the prescription of intravenous ATBs of a broader range than that required for respiratory infections. It is necessary to monitor compliance with national recommendations.